World cultures and geography - Milson, Andrew J.; Altoff, Peggy; Bockenhauer, Mark H.; Smith, Janet; Smith, Michael William; Moore, David W. (GEO, 2013)
The geographer's toolbox -- Physical & human geography -- North America geography & history -- North America today -- Central America & the Caribbean geography & history -- Central America & the Caribbean today -- South America geography & history -- South America today -- Europe geography & history -- Europe today -- Russia & the Eurasian republics geography & history -- Russia & the Eurasian republics today.